2023
DOI: 10.1002/anie.202300238
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilically Trapping Water for Preventing Polymerization of Cyclic Ether Towards Low‐Temperature Li Metal Battery

Abstract: Cyclic ether, such as 1,3-dioxolane (DOL), are promising solvent for low-temperature electrolytes because of the low freezing point. Their use in electrolytes, however, is severely limited since it easily polymerizes in the presence of lithium inorganic salts. The trace water plays a key role via providing the source (proton) for chain initiation, which has, unfortunately, been neglected in most cases. In this work, we present an electrophile, trimethylsilyl isocyanate (SiÀ NCO), as the water scavenger, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The organic components were mainly derived from the decomposition of DME, which is attributed to the protic acid produced by BF 4 − hydrolysis attacking the O containing lone pair electrons in the DME molecules. 56,57 First principles calculation showed that BF 4 − and DME had higher adsorption energy with different crystal planes of Zn compared to H 2 O, facilitating the formation of passivation layers rather than the HER (Fig. S7, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…The organic components were mainly derived from the decomposition of DME, which is attributed to the protic acid produced by BF 4 − hydrolysis attacking the O containing lone pair electrons in the DME molecules. 56,57 First principles calculation showed that BF 4 − and DME had higher adsorption energy with different crystal planes of Zn compared to H 2 O, facilitating the formation of passivation layers rather than the HER (Fig. S7, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the introduction of an anion receptor additive (TTFEB) into cyclic ether DOL effectively restrained its polymerization by capturing the PF 6 – anion . Given that trace water plays a crucial role by providing a source (protons) of chain initiation, we demonstrated a novel way to prevent polymerization by removing protonic acid through the nucleophilic addition reaction of water scavenger (Si–NCO) (Figure a). Si–NCO shows high water removal efficiency thanks to the strong electrophilic center induced by the electron-withdrawing conjugation effect.…”
Section: Pw For Cold Climatesmentioning
confidence: 99%
“…(a) Schematic representation of the design principle of a water scavenger to prevent DOL-based electrolyte gelation. Reprinted with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Pw For Cold Climatesmentioning
confidence: 99%
“…[9][10][11] Electrolyte engineering is one of the most relevant strategies in developing low-temperature, dendrite-free, and highly reversible LMAs, because electrolytes not only govern the Li + transport and de-solvation, but also affect the formation of the SEIs. [12,13] So far, a few electrolytes based on liquefied gas, [14,15] ether, [7,16] carbonate, [17,18] and/or acetate solvents with low freezing points have been reported for such a purpose. [19,20] It has also become clear that the solvation structure of Li + has significant influence on the low-temperature performance of LMAs.…”
Section: Introductionmentioning
confidence: 99%